Hubungan Antara Tayangan Sinetron "Anak Jalanan" Terhadap Perkembangan Sosial Anak Kelompok BDi TK Pertiwi 10 Cepoko Sumberlawang Sragen Tahun Ajaran 2015/2016 - Agustina, Intan Sulistiani; , Drs. Ilham Sunaryo , M.Pd (2016)
This study aims to determine the relationship between soap opera Anak Jalanan to the children social development This study is referred to as descriptive correlational research. Descriptive research is research that describes the variables in the study, with the correlational approach, because this study aims to determine the relationship between the two variables. According to the type of data collected, this study includes quantitative research, the data in the form of numbers or qualitative data. The results showed that have a positive influence and significant Parental Guidance that thitung (4.021)> t table (1.688), the Social Development Children this can give you an idea that the more harmonious and comfortable children feel Parental Guidance, it can provide a good influence on Social development Children.